2010
DOI: 10.1016/j.molcatb.2010.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Pistacia terebinthus extract: As a potential antioxidant, antimicrobial and possible β-glucuronidase inhibitor

Abstract: a b s t r a c tIn this study, inhibition of Escherichia coli glucuronidase (GUS) by a plant extract of Pistacia terebinthus was investigated. P. terebinthus (from Karaburun region in Turkey) leaf extract exhibits various bioactivities, such as antioxidant, antimicrobial and cytotoxic property because of its flavonoid, phenolic and alkaloid contents. HPLC analyses were performed to evaluate the composition of the extract and main flavonoid compounds such as luteolin, luteolin-7-glucoside and apigenin-7-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…The results on the live weight and weight gain of the birds indicated that supplementation of high level TFO (260 mg/kg) to diet improved live weight and weight gain, but not low level TFO (130 mg/kg). The improvement on the live weight and live weight gain in the high level TFO supplemented group may be related to the antibacterial agents, such as luteolin, luteolin-7-glucoside [10] and α-pinene [26] , antioxidant compounds, such as quercetin and α-tocopherol [9] , and high linoleic acid content of the TFO used in this study [8,16,17] . In other hand, Jang et al [27] reported that a commercial blend of EO showed a marked increase in digestive enzyme activities of the pancreas and intestinal mucosa from broiler chickens, leading in a significant growth performance.…”
Section: As Shown Inmentioning
confidence: 90%
See 1 more Smart Citation
“…The results on the live weight and weight gain of the birds indicated that supplementation of high level TFO (260 mg/kg) to diet improved live weight and weight gain, but not low level TFO (130 mg/kg). The improvement on the live weight and live weight gain in the high level TFO supplemented group may be related to the antibacterial agents, such as luteolin, luteolin-7-glucoside [10] and α-pinene [26] , antioxidant compounds, such as quercetin and α-tocopherol [9] , and high linoleic acid content of the TFO used in this study [8,16,17] . In other hand, Jang et al [27] reported that a commercial blend of EO showed a marked increase in digestive enzyme activities of the pancreas and intestinal mucosa from broiler chickens, leading in a significant growth performance.…”
Section: As Shown Inmentioning
confidence: 90%
“…(terebinth or turpentine tree), is a small tree, widely distributed in the Mediterranean region and west Asia [7][8][9][10] . It commonly grows on dry rock slopes and hillsides areas, pine forest, and maquis vegetation in the Mediterranean-, Aegean-, Black sea-, and Southeastern Anatolia region of Turkey [11][12][13] .…”
Section: Pistacia Terebinthus Lmentioning
confidence: 99%
“…Gram negative bacteria have a lipopolysaccharide outer membrane through which entry of molecules is achieved based on their size and shapes. Most of the compounds present in aqueous and methanolic extracts probably could not pass through the outer membrane to reach their site of action resulting in less inhibition (Fernandez-Agullo et al, 2013;Kavak et al, 2010). There was significant antibacterial activity in ethanol extract of all the plant parts tested (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in antimicrobial activity could be attributed to the presences of an additional external membrane surrounding the cell wall in Gram-negative bacteria which blocks the easy penetration of the bioactive compounds [23,24]. Among different extracts of different plants, methanol and acetone extracts displayed better and broad antimicrobial activity; a clear effect of the polarity of the solvents was envisaged.…”
Section: Antimicrobial Activity Of S Spontaneummentioning
confidence: 99%